Performance Evaluation of a Selection Combining Scheme for the Hybrid FSO/RF System - Wafaa Mohammed Ridha Shakir (IEEE Photonics Journal)
In this paper, an alternative implementation for the hybrid free-space optical (FSO)/radio frequency (RF) wireless communication system without requiring channel state information is presented. The proposed hybrid system transmits the same data with the same data rate over both links simultaneously. The well-known diversity selection combining scheme is implemented to combine the received signals in the electrical domain. New closed-form expressions for the average bit error rate and outage probability are derived in order to trace the system's performance over various channel turbulence conditions. The analysis of the proposed system's performance clearly indicates that the proposed system is advantageous as it exploits the complementary properties of the FSO and RF channels, even in strong turbulence conditions. In addition, the performance comparison demonstrates the proposed system's superior performance compared with the FSO-only system.